LATAR BELAKANG PEMBERIAN GELAR KEBANGSAWANAN DALAM NOVEL DJARINA KARYA ATTE SHENYLIA (TINJAUAN SOSIOLOGI SASTRA) - Fajrianti, Nurul (Fakultas Bahasa dan Sastra Indoensia, 2020)
The purpose of this study was to determine the background of giving the title of karaeng and daeng in Djarina's novel by Atte Shernylia Maladevi. This research uses descriptive qualitative method. The results of the research in the novel set in the past is that the title of karaeng is only given to royal descendants while the title of daeng is given to aristocratic families and also because of the position they have. The conclusion in this study is that the novel no longer reflects the awarding of titles at the present time which is no longer set in the kingdom, there has been a shift in the awarding of karaeng and daeng titles in today's society.